2019
DOI: 10.1016/j.ipej.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Non-fluoroscopic catheter ablation: A randomized trial

Abstract: BackgroundCatheter ablation provides curative treatment for tachyarrhythmias. Fluoroscopy, the method used for this, presents several risks. The electroanatomical mapping (MEA) presents a three-dimensional image without using X-rays, and may be adjunct to fluoroscopy.ObjectivesWe evaluated the possibility of performing catheter ablation with the exclusive use of electroanatomical mapping (MEA), dispensing with fluoroscopy. We compared the total time of procedure and success rates against the technique using fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Recurrence‐free survival rates were reported in 12 studies 3,5,6,8,10–12,17–22 . Mean procedure times were reported in 15 studies 3–8,10–13,17–22 . Complication rates were reported in 13 studies 3–7,9,11–13,19–22 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recurrence‐free survival rates were reported in 12 studies 3,5,6,8,10–12,17–22 . Mean procedure times were reported in 15 studies 3–8,10–13,17–22 . Complication rates were reported in 13 studies 3–7,9,11–13,19–22 .…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen of the 16 studies included in this meta‐analysis (2105 ZF, 3715 CF/LF) 3–9,11,12,17,19–22 reported acute procedure success rates. There was no significant difference in acute procedure success between ZF and CF/LF (OR: 1.10, 95% CI: 0.75–1.59, I 2 : 0.0%, p = .628) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Although, it requires X ray for visualization in most conventional cases, it can also be offered with fetal shield during the procedure, in the later half of pregnancy. 16 Three-dimensional mapping systems can also be used as the navigational modality minimizing or obviating the need for any exposure to ionizing radiation altogether. EPS-RFA has proven success and it has significantly reduced the mortality rate in SVT patients.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional form of catheter ablations involves the radiological modality called fluoroscopy. Fluoroscopy is utilized to position the catheter in the heart [ 28 ]. This presents a significant problem as the X-ray emissions from this procedure are dangerous to the fetus [ 29 ].…”
Section: Reviewmentioning
confidence: 99%